Prevalence of CTX-M Gene as an ESBL Marker in Clinical Klebsiella pneumoniae Isolates - Arafah Nurfadillah; Wahdaniar; Ummu Syauqah Al Musyahadah; Nur Insani Amir; Ade Irma; Miladiarsi; Tenri Ayu Adri (The Indonesian Institute of Science and Technology Research, 2023)
Klebsiella pneumonia is a bacteria that causes many negative impacts on health, primarily due to its tendency to develop antibiotic resistance. This research aims to identify the prevalence of the CTX-M gene as an ESBL marker of the Clinical Isolate of K. pneumoniae of Wahidin Sudirohusodo General Hospital. The samples consisted of 50 Clinic isolates of K. pneumoniae which fulfilled the inclusion and exclusion criteria. The research procedure consisted of DNA extraction, amplification, and agarose gel electrophoresis. The research results indicate that 38 samples (76%) are positive for the CTX-M gene, while 12 samples (24%) are negative or not found CTX-M gene. Thus, the prevalence of the CTX-M gene in K. pneumoniae resistant to beta-lactam antibiotics in Wahidin Sudirohusodo General Hospital is relatively high.